A Molecular Epidemiological Study of Human Parainfluenza 4 in the Western Cape, South Africa - Parsons, Jane (Division of Medical Virology, 2022)
Background Human parainfluenza 4 (HPIV 4) is a recognised cause of acute respiratory infection (ARI). However, there is no published data on the epidemiology of this virus in South Africa. This thesis describes the molecular epidemiology of HPIV 4 over a 4-year period (2014-2017). Respiratory samples from infants, children and adults presenting with respiratory illness in the Western Cape, South Africa were studied. Method A retrospective 4-year study using routine diagnostic samples from patients with ARI was conducted in Western Cape, South Africa. A database search of positive HPIV 4 samples detected by the Seegene Anyplex RV 16 diagnostic assay was extracted. Epidemiological information was recorded to determine age, gender, hospital ward (used as a proxy for disease severity), specimen type (upper or lower respiratory tract) and collection date (to indicate seasonality). To determine genetic evolution, novel primers targeting the haemagglutinin-neuraminidase (HN) in both HPIV 4 subtypes were designed to amplify a 733 bp and 738 bp sequence for HPIV 4A and HPIV 4B respectively. This product was then sequenced and aligned with known reference sequences from GenBank, using BioEdit. These aligned sequences were analysed using the phylogenetic analysis tool, MEGA 6, and Highlighter plots to determine sequence divergence events and evolution. A real-time PCR assay, targeting the phosphoprotein, was developed to rapidly distinguish subtype A and B viruses. Results HPIVs were the 6th most common respiratory viruses detected in diagnostic samples. In all, there were 312/7456 (4.2 %) HPIV 4 positive samples in patients with a median age of 12 months. Males had a higher infection rate. HPIV 4 was the most prevalent of the HPIVs accounting for 47% of all HPIVs. Respiratory infections due to HPIV 4 were seasonal, peaking in autumn and mid-winter (March to August). The overall prevalence of HPIV 4 increased over the study period. Of the HPIV 4-positive samples that were subtyped, 59 were subtype A and 26 subtype B. Both subtypes co-circulated during each season. 71 % of patients who were positive for HPIV 4 were co-infected with one or more additional respiratory virus with Adenovirus (27 %), Human Rhinovirus (23 %) and Bocavirus (19 %) as the most common. HPIV 1 and HPIV 3 were both able to co-infect patients with HPIV 4, but no co-infections with HPIV 2 were detected. Phylogenetic trees constructed using neighbour joining (NJ) method showed that most of the South African HPIV 4 subtypes did not group with the closest significant reference sequences from GenBank. The phylogenetic tree for HPIV 4A revealed 4 genetic groupings. There were many nucleotide changes increasing with time as well as a non-synonymous change in HPIV 4A, at location N161D. HPIV 4B had an amino acid change in location G198R in the HN protein sequenced. Conclusion HPIV 4 with an overall prevalence of 4 % over the study period was identified as a significant cause of ARI in the Western Cape, South Africa. Mono-infection with HPIV4 was associated with severe disease. In hospitalized infants who were HPIV 4 positive, between ¼ to 1/3 were from patients in ICU. Of these almost half (46 %) had HPIV 4 as a single infection. Further studies are needed to fully understand the molecular epidemiology of this infection.